Understanding Determinants of Individual Intention to Invest in Digital Risky Investment - Abdillah, Willy; Permatasari, Rika; Hendrawaty, Ernie (JDM (Jurnal Dinamika Manajemen), 2019)
This study examines the effect of emotional intelligence, the locus of control, and risk aversion on intention to risky investment with financial literacy as moderating effect. This study uses 98 investors distributed by online questionnaire. Data examined using Partial Least Square (PLS) technique. The results show that the emotional intelligence, the locus of control have a positive effect and risk aversion and financial literacy have a negative effect on intention to a risky investment. However, there is no moderating effect of financial literacy on those direct effects. The implication for stakeholder and further research are discussed.